Smoking and FGFR2 rs2981582 variant independently modulate male breast cancer survival: A population-based study in Tuscany, Italy. (August 2018) - Zanna, Ines; Silvestri, Valentina; Palli, Domenico; Magrini, Alessandro; Rizzolo, Piera; Saieva, Calogero; Zelli, Veronica; Bendinelli, Benedetta; Vezzosi, Vania; Valentini, Virginia; Bianchi, Simonetta; Ottini, Laura; et al.
Abstract: Aim: Male breast cancer (MBC) is a rare disease and recommendations for its clinical management are often extrapolated from those for female breast cancer, even if breast cancer (BC) has different characteristics in the two sexes. The purpose of this study was to assess the influence of several individual characteristics including clinico-pathological, lifestyle and genetic factors on overall survival (OS) of a relatively large and well characterized population-based series of 166 MBCs enrolled in Tuscany. Methods: We genotyped MBC cases at BRCA1 /2 genes and at 9 candidate BC susceptibility SNPs. Kaplan-Meier method and multivariate Cox regression, adjusted for several individual characteristics were used. To reduce a possible selection bias related to the interval between diagnosis and enrolment of MBC cases into the study, we used the date of blood donation as the date of the start of observation for survival analysis. Results: Only smoking habits had a significant effect on OS at 10 years (for current smokers, HR: 3.34; 95% CI 1.45–7.68; p = 0.004), while lymph node status fell short of reaching statistical significance (for pN positive, HR: 2.07; 95% CI 0.93–4.55; p = 0.07). In the same multivariate analysis we found a significantly higher OS in cases with FGFR2 rs2981582 variant in the dominant transmission model (HR: 0.29; 95% CI: 0.13–0.62; p = 0.028). A sensitivity analysis with left truncation showed similar results. Conclusions: Our results may contribute to shed light on factors influencing MBC survival suggesting an important role for cigarette smoking and FGFR2 rs2981582 variant, and provide clues for better patient management. Highlights: A population-based series of 166 men with breast cancer are included in the study. Smoking habits have a significant effect on overall survival at 10 years. FGFR2rs2981582 variant show a significant decreased risk of death at 10 years.